THE INFLUENCE OF INVESTMENT MOTIVATION, INVESTMENT KNOWLEDGE, AND FINANCIAL LITERACY ON INVESTMENT INTEREST - Fortunatus, Angela Eunike; Pamungkas, Ary Satria (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to ascertain how investment motivation, investment knowledge, and financial literacy contribute to the millennial generation's interest in investing in Bandung. This study's sample consists of Bandung's millennials who are interested in stock investing. The purposive sampling method was used to select 220 respondents for the study's sample. Structural Equation Modelling (SEM) was used for data analysis techniques. Using the quantitative research method, a descriptive research design was used in this study. This study found that investment interest is influenced by investment motivation, investment knowledge, and financial literacy.